Cognitive restructuring group counseling to increase adversity quotient as an effort to prevent suicide in students - Utami Fitri, Hartika; Ningsih, Chairunnisah Putri Ayu; Julianti, Javica; Khairunisya, Dwi Amanda; Maharani, Aisyah; Alamsyah, Bagus Wahyu (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
The issue of suicide has recently become a global problem while student For preventing the occurrence possibility kill a high adversity quotient is needed . The purpose of the research is for know the effectiveness counseling Counseling Restructuring Engineering Group Cognitive For Improving Student Adversity Quotient. Second , knowing expression students who have a low adversity quotient . Research methods This use approach mix method with embedded design method mixture with embedded experimental. Subject research A total of 10 people were taken with technique purposive sampling from a total population of 227 students . Data collection techniques using (adversity quotient questionnaire ) with a total of 25 statement items . Data analysis techniques using technique quantitative data analysis ( Wilcoxon test ), qualitative data analysis (Miles & Huberman ), techniques mix method data analysis . Research results show counseling Restructuring Engineering Group Cognitive  effective increase Adversity Quotient in students.